Association of Thyroid Dysfunction with Mood Disorders in an OPD setting (Journal of Psychiatrists' Association of Nepal, 2014)
Background and Objectives: Thyroid dysfunction is common among patients with mood disorders. The main purpose of this study is to estimate the prevalence of thyroid dysfunction among patients with various types of mood disorders. Materials and Methods: The study compromised of 50 patients meeting the inclusion and exclusion criteria selected by simple random sampling technique who attended the psychiatry OPD at B P Koirala Institute Of Health Sciences Dharan, Nepal. These patients were classified into different types of mood disorders according to ICD-10 DCR Criteria. Nineteen patients (38%) were diagnosed BPAD, fourteen patients ( 28%) as Depressive Disorder and the rest as single episode mania , Recurrent depressive disorder and dysthymia. Results: Out Of a total 50 cases, Fifteen Patients(30%) were found to have some form of thyroid dysfunction , the most common being subclinical hypothyroidism seen in 22% and the rest 8% with overt hypo/hyperthyroidism cases. This data is clearly /significant higher than the general population. However, there was no significant association found between socio-demographic variables and mood disorders with thyroid dysfunction. Conclusions: This study shows that thyroid dysfunction is common among patients with mood disorders though larger studies in the community setting are required for further evaluation. DOI: http://dx.doi.org/10.3126/jpan.v3i1.11348 J Psychiatrists’ Association of Nepal Vol .3, No.1, 2014: 23-28